(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper presents a critical review of three theoretical perspectives on language maintenance (LM) and language shift (LS) in minority language contexts. These three perspectives are (1) LS and subtractive bilingualism, (2) reversing LS and additive bilingualism, and (3) a critical perspective on bi/multilingualism. The review aims to demonstrate that much of the LM/LS literature as reflected in the first two perspectives (i.e., LS and subtractive bilingualism, and reversing LS and additive bilingualism) has been dominated by an essentialised view of language and its related concepts (i.e., identity and community) as whole, separate and autonomous entities within the bounds of nationstates. Such perspectives tend to reinforce a simplistic view of LM/LS as an all-or-nothing phenomenon and to advance its pessimistic outlook as language loss or language death. Hence, for a more fruitful framework, this paper presents a critical perspective on bi/ multilingualism that draws on postmodern and poststructuralist theories (Heller 2007a, 2012; Makoni and Pennycook 2007; Pennycook 2010). By seeking to investigate bi/ multilingual speakers’ local language ideologies and practices, this critical perspective enables not only a reconceptualisation of language, identity and community but also a more realistic and hopeful vision of bi/multilingualism in our pluralist, diverse, transnational and translocal world.